Effect of Spinal Correction Surgery on Lower Limb Strength in Idiopathic Adolescent Scoliosis - Laett, Conrado Torres; Visconti, Rogério dos Reis; Meirelles, Ricardo de Souza Portes; Santos, Lenifran de Matos; Cossich, Victor Rodrigues Amaral; Silva, Sidnei Cavalcante da (Revista Brasileira de Ortopedia, 2023)
Objectives To analyze the lower limb strength in both untreated and surgically treated adolescent idiopathic scoliosis (AIS) patients and examine its correlation with the distance covered in a six-minute walking test (6MWT).Methods A total of 88 participants (n = 30 pre-surgery AIS patients, n = 30 post-surgical AIS patients, and n = 28 control) underwent a 6MWT and a muscle strength assessment. The lower limb strength was measured at the knee joint using the knee extension (KE) and knee flexion (KF) peak torque (PT) measurements.Results The control group covered a greater distance in the TC6 compared to both the pre-surgical (534 ± 67 m) and post-surgical (541 ± 69 m) groups, with a distance of 612 ± 70 m (p < 0.001). No differences were observed in KE PT (pre: 2.1 ± 0.63, post: 2.1 ± 0.7, control: 2.2 ± 0.7 Nm.kg−1, p = 0.67) or KF PT (pre: 1.0 ± 0.3, post: 1.1 ± 0.3, control: 1.1 ± 0.5 Nm.kg−1, p = 0.46). A moderate positive correlation was observed between KE PT and 6MWT distance (r = 0.53, p < 0.001), as well as a low positive correlation for KF PT (r = 0.37, p = 0.003) with 6MWT distance.Conclusion This study highlights the importance of lower limb maximal strength in the functionality of AIS patients. Our findings suggest that exercise programs aimed at enhancing lower limb strength, especially the KE, could improve the walking capacity of AIS patients. These results provide useful information for designing purposeful exercise programs for AIS patients with walking deficits.
Keywords: adolescent; scoliosis; muscle strength; exercise test